On the investigation of optical soliton solutions of cubic-quartic Fokas-Lenells and Schrodinger-Hirota equations - Ozisik, Muslum; Onder, Ismail; Esen, Handenur; Cinar, Melih; Ozdemir, Neslihan; Secer, Aydin; Bayram, Mustafa (ELSEVIER GMBH, 2023)
Purpose: When it comes to third and higher-order dispersion, the Schrodinger-Hirota equation is one of the main models developed outside the classical NLSE management models for optical soliton transmission. The cubic-quartic Fokas-Lenells equation is also one of the recently developed equations, which has importance in the field of telecommunications regarding optical soliton transmission in the absence of chromatic dispersion. In this study, in order to examine the optical solitons, the Schrodinger-Hirota equation in the presence of the chromatic dispersion and the cubic-quartic Fokas-Lenells equation discarding the chromatic dispersion were investigated. For this intent, by obtaining certain soliton types using the unified Riccati equation expansion method (UREEM), optical soliton solutions were obtained for both models and graphical representations and comments were made.Methodology: By developing appropriate computer algorithms and applying UREEM in the following ways, symbolic calculation software was made and analytical optical soliton solutions were obtained. Findings: Through computer algebra software, we plotted the obtained results via 3D, 2D views and we also illustrated the investigation of wave behavior caused by parameter change on 2D graphics.Originality: Different soliton behavior under the parameters effect of the Schrodinger-Hirota equation having chromatic dispersion and the cubic-quartic Fokas-Lenells equation is investi-gated and the obtained results are reported.
Keywords: Optical solitons; The third and fourth-order dispersion; Chromatic dispersion; Kerr law; Unified Riccati equation expansion method; FIBER BRAGG GRATINGS; POLARIZATION-MODE DISPERSION; GROUP-VELOCITY DISPERSION; PORSEZIAN-DANIEL MODEL; CONSERVATION-LAWS; PERTURBATION; DARK; NONLINEARITY; STATIONARY; Optics